O negro, educação e as relações étnico-raciais no ensino fundamental II em uma escola estadual de Mossoró-RN - Silva, Vanessa Cristina de Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
Since the beginning, in the formation of the Brazilian society, the black population has been discriminated and excluded through a system of domination and imposition of the white ethnicity on the others. Comfortable with the myth of racial democracy, Brazilian society and even the education system of our country omitted to address the issue on racism that exists in our guts until these days. Problematize: How has Education for Ethnic-Racial Relations in the context of Elementary School II been doing in a School of the State system in Mossoró-RN? Its general objective is: To analyze how black education has been doing and its insertion in the school setting as of the ethnic-racial relations. As specific goals: a) to understand black identity in Brazil and how it has been understood in basic education; b) discuss how pedagogical practice can influence the materialization of black identity; and c) Reflect on the importance of Education for ethnic-racial relations in the context of primary education II. This research is based on authors as: Freyre (1975); Sodré (1999), Fernandes (2008); Munanga (2005) and Gomes (2008) and others still, as well as using official documents, nº 10.639 / 03 that amends the LDB (1996), as well as the National Curricular Guidelines for Ethnic-Racial Relations Education (DCNERER) promulgated in 2004. Data were obtained through a semi-structured interview, with 03 teachers from Elementary education II. Mixed questionnaires were also applied, with 11 students from the institution investigated. The results indicate that black people in Brazil have been the victims of numerous prejudices and their insertion in the social setting does not occur in a way equivalent to white ethnicity, for example. It is noted that many of their rights as citizens are denied and neglected, including the right to education. The data made it possible to understand that the school plays a fundamental role in the re-signification and valorization of black culture. However, the school's and the teacher staff position in not taking discussions in favor of Education for Ethnic-Racial Relations ends up contributing to the reproduction and perpetuation of racism among students and consequently in society.
Monografia
Keywords: Preconceito; Racismo; Educação para as Relações Étnico-Raciais em Mossoró-RN; Mito da Democracia Racial; Negro; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL